Ethical questions related to using netnography as research method - Anne-Marie Tuikka; Chau Nguyen; Kai K. Kimppa (UK Engineering and Physical Sciences Research Council, 2022)
Netnography is a relatively new research method, which adapts research techniques of ethnography to study cultures and communities through computer-mediated communications. It has become a popular research method in marketing research during the early 21st century. However, the use of netnography in the field of information systems (later referred as IS) has not been studied to great extent. Thus, we have conducted a systematic literature review to investigate the ethical practices of netnographic research in the field of IS.
To analyse the ethical practices of netnographic research and discussion surrounding it, we have collected 52 articles which use netnography either as their sole research method or as their completing research method. These articles were selected from 77 IS journals. Our findings indicate that netnography is an emerging research method which is still searching the shape of its ethical guidelines. Researchers, who use netnography, do not completely agree on the ethically just manner of conducting netnography. However, it is apparent that certain ways of conducting netnography are often considered to be ethically just where as some other ways might be often considered to not be ethically just.